Estudio de conexiones precalificadas y su incidencia en el diseño sismo resistente de edificaciones irregulares - Sánchez Guevara, Nelson Hernan (2022)
Ecuador is a country with high seismic activity. In 2016 it was affected by a seismic event which was generated as a result of a phenomenon produced between the subduction of the Nazca plate and the South American plate, which left substantial economic, human and building losses, this being a major factor of utmost importance for research in the field of structural engineering. In the present research work, a seismic-resistant analysis of three irregular buildings of low, medium and high height, formed by a lateral load resistant system of special structural steel SMF moment resisting frames, composed of HEB type columns and IPE beams, was carried out. To start the project, an analysis of the structural configuration of the proposed buildings was carried out to then apply the considerations established by the Ecuadorian construction standard to take into account the corresponding cases of irregularity in the buildings, both in elevation and in plan. Then we proceeded to solve the structures by means of a linear static and dynamic analysis, obtaining results that show an adequate structural behavior and comply with the mandatory normative checks, such as checking the floor drifts, the verification of the strong column - weak beam criterion and the design of its structural elements. Steel connections are of great importance to guarantee the seismic-resistant behavior of buildings. In areas of high seismicity, it is necessary to use special moment-resistant portal frame systems and that their connections are prequalified, which will guaranteexxvii the adequate formation of the plastic patellas contributing to obtain as a result an appropriate behavior in the nonlinear range. Once the structural designs of the proposed buildings were finalized, two prequalified connections were designed, the Bolted Flange Plate Connection (BFP) and the Reduced Beam Section Connection (RBS) described in the AISC 358-16 standard. The connections were designed manually complying with all the parameters established in the AISC 358-16 standard to finally perform their respective validation and comparison of the results obtained through the use of a software specialized in the design of steel connections, obtaining similar results.